"PEDAGOGICAL CONFLICTOLOGY IN THE DEVELOPMENT STRATEGY OF PRESCHOOL EDUCATIONAL ORGANIZATIONS: THEORY, PRACTICE AND PROBLEMS" - Zulpukorova Parvina Ruzmat qizi (TADQIQOTLAR, 2025)
Annotation This article covers the theoretical and practical aspects of pedagogical conflictology. It provides a detailed analysis of the types of conflicts that arise in the pedagogical process, their causes, methods of identification and diagnosis, strategies for preventing and resolving conflicts. It also demonstrates the effective use of pedagogical conflictology through practical examples from preschool and school educational environments. The article provides practical recommendations for understanding and resolving pedagogical conflicts and is intended as a useful guide for pedagogical personnel, parents, and specialists working in the field of education.